Cost drivers and functions for municipal solid waste collection systems in Ghana - Sulemana, Alhassan; Amponsah Donkor, Emmanuel; Oduro-Kwarteng, Sampson (International Journal of Engineering and Technology, 2018)
The collection of municipal solid waste accounts for 60% to 80% of total management cost. This study determined the factors driving operating cost and developed cost functions for municipal solid waste collection systems in Ghana. Data on cost variables from seventy systems were used to estimate the parameters of log-linear cost functions. Results from the study led to the conclusion that quantity of waste collected, fuel consumed and distance travelled increase significantly and explain about 63.0% of the variation in operating cost. The amount of fuel consumed and quantity of waste collected varied significantly and explained about 67.4% of the variation in operating cost of systems from low waste generating sources. For high waste generating sources, the distance travelled, fuel consumed and quantity of waste collected significantly and better explained (85.4%) the variation in operating cost. This can be attributed to the fact that such systems are from places with better facilities. The cost function for high waste generating sources can comparatively better aid decision making in terms of operations, management, investment and policy actions. Cost-effective solid waste collection schemes should therefore consider efficient management of fuel consumed, quantity of waste generated and distance travelled.Â Â